2017
DOI: 10.1097/j.pain.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to insufficient sleep alters processes of pain habituation and sensitization

Abstract: Chronic pain conditions are highly comorbid with insufficient sleep. While the mechanistic relationships between the 2 are not understood, chronic insufficient sleep may be 1 pathway through which central pain-modulatory circuits deteriorate, thereby contributing to chronic pain vulnerability over time. To test this hypothesis, an in-laboratory model of 3 weeks of restricted sleep with limited recovery (5 nights of 4-hour sleep per night followed by 2 nights of 8-hour sleep per night) was compared with 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 44 publications
1
62
0
1
Order By: Relevance
“…The mechanistic relationship between sleep problems and chronic pain is not yet clear. One suggested mechanism is that insufficient sleep alters the processes of pain habituation and sensitization, and increase vulnerability to chronic pain [ 18 ]. The purpose of using a wash-out period was to distinguish between regional pain (presumably without central sensitization) and CWP (where disturbed pain systems are common).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanistic relationship between sleep problems and chronic pain is not yet clear. One suggested mechanism is that insufficient sleep alters the processes of pain habituation and sensitization, and increase vulnerability to chronic pain [ 18 ]. The purpose of using a wash-out period was to distinguish between regional pain (presumably without central sensitization) and CWP (where disturbed pain systems are common).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that sleep predict pain prognosis, [ 15 17 ]. The underlying mechanisms for why disturbed sleep would predict pain prognosis is not yet fully established, however there are studies indicating that sleep disturbances influence pain sensitization and pain inhibitory systems [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Basic research provides evidence that low sleep quality affects nociception with decreased pain thresholds, increased subjective pain ratings and also cortical processing. [9][10][11][12][13][14][15][16] It is assumed that especially the functionality of the pain inhibiting circuits is negatively affected by poor sleep quality. Curbed activity of the endogenous pain inhibition leads to an imbalance of excitatory and inhibitory activation which in turn does not only increase pain sensitivity in healthy individuals but also worsens pain symptoms in patients with acute and chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…In mechanical, interventional and epidemiological studies alike, considerable effort has been devoted to progressively shed light on the relationship between sleep and pain [8,[11][12][13][14][15][16][17]. For example, a recent meta-analysis with pooled estimates from 37 studies using polysomonography in populations with persistent pain, reported a 72% prevalence of insomnia [18].…”
Section: Introductionmentioning
confidence: 99%